Principles and pratice of automatic process control - Smith, Carlos A. (John Wiley & Sons, 2006)
Highly practical and applied, this Third Edition of Smith and Corripio's Principles and Practice of Automatic Process Control continues to present all the necessary theory for the successful practice of automatic process control. The authors discuss both introductory and advanced control strategies, and show how to apply those strategies in industrial examples drawn from their own professional practice.